BUDAYA POPULIS DALAM DAKWAH ISLAM: Simbolisasi Muslim Urban dalam Film Ketika Tuhan Jatuh Cinta - D. I. Ansusa Putra; Mila Wahyuni; Jam’ah Alfi Hidayah (Borneo : Journal of Islamic Studies, 2021)
Urban Muslims are one of the unique communities in society. This can be seen from the symbolization of urban Muslims that is different from traditional Muslim societies, in Islamic films. Urban characteristics in Indonesia's populist culture show the dialectic of urban Muslim life in the face of a socio-religious context. Urban Muslims are required to actualize themselves in complex urban life with social class conflicts, social deviations, and cultural orientations. This article aims to identify the symbols of urban Muslims in film when God falls in love using interpretive symbol analysis using Roland Barthes' semiotic theory. This article concludes that the symbolization of urban Muslims in populist culture Islamic film is concentrated on three things: 1) visual communication 2) narrative 3) storyline contextualization. Urban Muslims have unique symbol characteristics 1) religious tolerance 2) anti-establishment 3) self-actualization 4) self-satisfaction oriented.